Development Strategy of Small Industry of Typical Food as Supporting Tourism Sector - Hanif, Luqman; Fafurida, Fafurida (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
The purpose of this research is to formulate the development strategy of the small industry of tamarillo processed typical food in Kejajar District that faces the marketing obstacles, the simple technology, and the lack of capital. This research also aims at analyzing the position and the development strategy of tamarillo processed product as the typical food from Dieng Plateau. The SWOT analysis is used at the first stage and the Ansoff Matrix analysis is used at the second stage. The result of SWOT analysis indicates that the position of small industry is in quadrant II, which supports the growth strategy through horizontal integration. The strategy can be implemented by cooperating with the similar small industries and the Department of Tourism and Culture of Wonosobo Regency for marketing. The Ansoff Matrix analysis indicates that the position of tamarillo processed product is seen as the new typical food in Kejajar District, so, the main strategy for the small industry is market development strategy to increase the market share and to create the brand image to the tourists.